Development of a low-level 37Ar calibration standard. (March 2016) - Williams, R.M.; Aalseth, C.E.; Bowyer, T.W.; Day, A.R.; Fuller, E.S.; Haas, D.A.; Hayes, J.C.; Hoppe, E.W.; Humble, P.H.; Keillor, M.E.; LaFerriere, B.D.; Mace, E.K.; et al.
Abstract: Argon-37 is an environmental signature of an underground nuclear explosion. Producing and quantifying low-level 37 Ar standards is an important step in the development of sensitive field measurement instruments. This paper describes progress at Pacific Northwest National Laboratory in developing a process to generate and quantify low-level 37 Ar standards, which can be used to calibrate sensitive field systems at activities consistent with soil background levels. This paper presents a discussion of the measurement analysis, along with assumptions and uncertainty estimates. Highlights: A process is described for producing Bq quantities of Ar-37 using D–T generator. Length-compensated proportional counting is used to quantify the specific activity. We discuss Ar-37 standards related to the Comprehensive Nuclear-Test Ban Treaty. An uncertainty analysis, following the ISO GUM guidelines, is presented.